An incoherent feed-forward loop coordinates nitrate uptake and tillering in wheat - Weiya Xu; Yongming Chen; Yanxiao Niu; Bin Liu; Dejie Du; Xining Ning; Tong Huan; Yilan Zhou; Wensheng Ke; Lingfeng Miao; Weilong Guo; Mingming Xin; et al. (Molecular Plant, 2025)

In situ electrocatalytic nitrate-to-nitrite conversion-driven anammox in MBRs for extremely efficient ammonium-containing wastewater treatment - Lingfeng Ni; Peifang Wang; Gang Zhou; Zibin Li; Yayi Wang (Water Research, 2025)

Urban vegetation productivity under climate change and increasing urbanization: Insights from both urban-rural comparison and trend analysis for global cities - Jiuyi Chen; Bo Qiu; Weidong Guo; Xin Miao; Yipeng Cao; Zhihan Zhao; Siwen Zhao; Lingfeng Li; Yueyang Ni; Shihan Tang; Limei Yang (Urban Forestry & Urban Greening, 2025)

Correction: Divergent dominant physical processes of extreme heatwaves in northern and southern China - Yueyang Ni; Bo Qiu; Yipeng Cao; Xin Miao; Lingfeng Li; Jiuyi Chen; Siwen Zhao; Xiaohui Tian; Weidong Guo (Climate Dynamics, 2025)

Machine learning-based prediction of terrestrial heat-flow across mainland China - Chang Ni; Shan Xu; Xiangyun Hu; Xianchun Tang; Wenglong Zhou; Lingfeng Gao (Tectonophysics, 2025)

Near-complete assembly and comprehensive annotation of the wheat Chinese Spring genome - Zijian Wang; Lingfeng Miao; Kaiwen Tan; Weilong Guo; Beibei Xin; Rudi Appels; Jizeng Jia; Jinsheng Lai; Fei Lu; Zhongfu Ni; Xiangdong Fu; Qixin Sun; et al. (Molecular Plant, 2025)

Divergent dominant physical processes of extreme heatwaves in northern and southern China - Yueyang Ni; Bo Qiu; Yipeng Cao; Xin Miao; Lingfeng Li; Jiuyi Chen; Siwen Zhao; Xiaohui Tian; Weidong Guo (Climate Dynamics, 2025)

Insight into the mechanisms and in-plane reaction heterogeneity of the dynamic response of proton exchange membrane fuel cells - Lingfeng Ye; Diankai Qiu; Meng Ni; Linfa Peng (Chemical Engineering Journal, 2024)

GNSS spoofing detection method based on the intersection angle between two directions of arrival (IA‑DOA) for single-antenna receivers - Shimiao Chen; Shuyan Ni; Lingfeng Cheng; Tuofeng Lei; Xin Song (GPS Solutions, 2024)

Interfacial electronic engineering of heterostructured Co2P-MoNiP/NF nano-sea-urchin catalysts for efficient and stable hydrogen evolution via water/seawater splitting - Yifan Zhao; Hua Zhang; Ji Chen; Shuwen Zhao; Min Xi; Lingfeng Yang; Youyu Long; Zitao Ni; Yao Zhou; Anran Chen (Chemical Engineering Journal, 2023)

The Clam Cyclina sinensis (Gmelin) Phylogeography Study with 28S rRNA Gene and Potential of Nuclear rRNA Genes in Genetic Assessments of Molluscs - Gang Ni; Qi Li; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2022)

Insights into fouling behavior in a novel anammox self-forming dynamic membrane bioreactor by the fluorescence EEM-PARAFAC analysis - Yijing Zhu; Lijuan Cao; Lingfeng Ni; Yayi Wang (Environmental Science and Pollution Research, 2020)

Comparative phylogeography in marginal seas of the northwestern Pacific - Gang Ni; QI Li; Lingfeng Kong; Hong Yu (Molecular Ecology, 2014)
The maturation of marine phylogeography depends on integration of comparative information across different regions globally. The northwestern Pacific, characterized by unique tectonic setting, however, is still underrepresented. This study seeks to highlight its phylogeographical history based on the available population data, focusing on three seas: the East China Sea ( ECS ), the South China Sea ( SCS ) and the Sea of Japan ( SOJ ). We first conducted a literature survey to evaluate current research efforts and then reanalysed the population structure, historical demography and genealogy for two selections of studies (namely ‘the ECS category’ and ‘the multiple‐sea category’) to elucidate the evolutionary processes within and across the seas, respectively. For the ECS category, the meta‐analyses revealed most studies displayed a shallow phylogeny, indicating a single origin from the sea. Significant population structure was commonplace, particularly in molluck and crustacean studies, with proportions of 89% and 80%, respectively. Nearly all studies selected showed signals of population expansion: the times estimated were closely linked to a period of ~120–140 Kya rather than the last glacial maximum. For the latter category, divergent intraspecific lineages appeared among seas and overlapped in the adjacent regions, a pattern implying each sea had served as an independent refugium during glaciations. The genetic splits, however, were estimated to arise from separate events dating from late Miocene to middle Pleistocene. As phylogeography is still in its infancy in the region, more effort is needed to test and complement the general rules abstracted here. Finally, challenges and prospects were discussed to accelerate further research.

Isolation and characterization of 19 microsatellite markers from the Chinese surf clam (Mactra chinensis) - Lehai Ni; Qi Li; Lingfeng Kong (Conservation Genetics Resources, 2010)